2010
DOI: 10.5713/ajas.2010.10329
|View full text |Cite
|
Sign up to set email alerts
|

The Endocrine Regulation of Chicken Growth

Abstract: The somatotropic axis plays a key role in proliferation and differentiation of avian organs during both pre-and posthatching periods. This review discusses the complexity of regulation of the endocrine system for chicken development and growth by growth hormone (GH), insulin-like growth factor (IGF), and IGF binding protein (IGFBP). In addition, the thyrotropic axis, including thyrotropin-releasing hormone (TRH) and thyroid hormones (T 4 and T 3 ), is also involved in the GH-secreting pattern. In mammals, IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 103 publications
1
22
0
Order By: Relevance
“…Growth hormone (GH) is necessary for differentiation of muscle, adipocytes, and other cells to modulate development and growth (Kim 2010). In the present study, increased expression of hepatic cGH gene was observed in AA injected embryos during pre-hatch period, indicating an effective way to increase the size of the chick without decreasing hatchability (Ohta et al 1999).…”
Section: Discussionmentioning
confidence: 56%
“…Growth hormone (GH) is necessary for differentiation of muscle, adipocytes, and other cells to modulate development and growth (Kim 2010). In the present study, increased expression of hepatic cGH gene was observed in AA injected embryos during pre-hatch period, indicating an effective way to increase the size of the chick without decreasing hatchability (Ohta et al 1999).…”
Section: Discussionmentioning
confidence: 56%
“…An inverse pattern revealed greater IGF-I mRNA transcription in the liver of broilers fed high methionine concentration. The GHR expression may be reduced directly by the amount of GH in this organism, but also by the influence of GH that can occur via IGF-I (Kim et al, 2010). Therefore, diets with higher methionine concentrations increased IGF-I concentrations and decreased GHR gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…bold shows EcoRV restriction sites; box shows g.2248G>A GH SNP target (GenBank accession number: AY461843.1) . Kim et al (2010) explain that the GH-GHR complexes activate hepatic IGF-I secretion, which stimulates the differentiation and proliferation of bone and muscle cell. Our study in the GH|EcoRV genotyping generated the GG genotype predominantly (0.749), the AG genotype as a second majority (0.247), and almost no AA genotype was found (0.005) in overall population.…”
Section: Discussionmentioning
confidence: 99%
“…The chicken growth hormone is widely known as a major hormone that acts directly on chicken development and metabolism (Kim, 2010) and relates to egg production (Su et al, 2014;Vu & Ngu, 2016). GH regulates a variety of physiological functions such as growth, body composition, egg production, aging, reproduction, sexual maturation, and functionality of the central nervous system (Gosney et al, 2012;Hrabia et al, 2008;Hull & Harvey, 2014;Stephen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%